Gill Structure of Ompok hypophthalmus Bleeker from the Tarai River, RiauProvince - Febi Nuari Safana; Windarti Windarti; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Ompok hypophthalmus Bleeker is one of fish that live in the Tarai River, a polluted river in Riau. The quality of water in the river may affects the fish health status in general, including its gill structure. A study aims to understand the histological structure of the gill of fish living in the Tarai River has been conducted in April 2018. The gill were histologically processed through alcohol series, 6mm sliced and HE stained. Types of abnormality in the gill was noted and the Histopathological Alteration Index (HAI) was calculated. Results shown that abnormality present in the gill were hyperplasia, broken epithelium, hemorrhage and curling secondary lamella. The average of HAI value was 9.7 indicates that the gill of O. hypophthalmus from the Tarai River was slightly damage.Keyword: Sheatfish, Histopathological Alteration Index, gill abnormality, polluted  river